Vampires : myths and metaphors of enduring evil - Day, Peter (At the interface/probing the boundaries, 2006)
In the modern world vampires come in all forms: they can be perpetrators or victims, metaphors or monsters, scapegoats for sinfulness or mirrors of our own evil. What becomes obvious from the scope of the fifteen essays in this collection is that vampires have infiltrated just about every area of popular culture and consciousness. In fact, the way that vampires are depicted in all types of media is often a telling signifier of the fears and expectations of a culture or community and the way that it perceives itself; and others. The volume's essays offer a fascinating insight into both vampires.